A ROBUST APPROACH FOR EFFECTIVE SPAM DETECTION USING SUPERVISED LEARNING TECHNIQUES - V.VENKATA SATYA SURYA,T.Nagajyothi, Komminni sushma, Gadde sahitha, Baddamprajwala (Pegem Journal of Education and Instruction, 2023)
With the ascent of texting applications, Short Message Administration (SMS) has reduced in pertinence and is currently transcendently utilized by specialist co-ops, organizations, and associations for showcasing and spam. An eminent pattern in spam is the utilization of local language content written in English, which muddles identification and sifting.